A Picture of the Healthful Food Environment in Two Diverse Urban Cities - Rebecca E. Lee; Katie M. Heinrich; Ashley V. Medina; Gail R. Regan; Jacqueline Y. Reese-Smith; Yuka Jokura; Jay E. Maddock (SAGE Publishing, 2010)
Background Local food environments influence fresh produce purchase and consumption, and previous research has found disparities in local food environments by income and ethnicity. Other existing studies have begun to quantify the distribution of food sources, but there has been limited attention to important features or types of healthful food that are available or their quality or cost. Two studies assessed the type, quantity, quality and cost of healthful food from two diverse urban cities, Kansas City, Kansas and Missouri and Honolulu, Hawaii, and evaluated differences by neighborhood income and ethnic composition. Method A total of 343 food stores in urban neighborhoods were assessed using the one-page Understanding Neighborhood Determinants of Obesity (UNDO) Food Stores Assessment (FSA) measuring healthful foods. US Census data were used to define median household income and ethnic minority concentration. Results In Study 1, most low socioeconomic status (SES), high ethnic minority neighborhoods had primarily convenience, liquor or small grocery stores. Quality of produce was typically lower, and prices of some foods were more than in comparison neighborhoods. In Study 2, low SES neighborhoods had more convenience and grocery stores. Farmers' markets and supermarkets had the best produce availability and quality, and farmers' markets and pharmacies had the lowest prices. Conclusions Messages emphasizing eating more fruits and vegetables are not realistic in urban, low SES, high ethnic concentration neighborhoods. Farmers' markets and supermarkets provided the best opportunities for fresh produce. Increasing access to farmers' markets and supermarkets or reducing prices could improve the local food environment.